STRATEGI PENGELOLAAN ZAKAT UNTUK PENDIDIKAN OLEH BAZNAS KOTA JAMBI MELALUI PROGRAM JAMBI KOTA CERDAS - Novita Dewi Pertiwi; A. A. Miftah; Ahmad Syahrizal (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This thesis discusses the problems, namely: What is the strategy for managing zakat for education by Baznas Jambi City through the Jambi Smart City Program, what are the supporting and inhibiting factors for managing zakat for education at BAZNAS Jambi City and what is the impact of managing zakat for education at BAZNAS Jambi City. With the aim of knowing the strategy for managing zakat for education by the Jambi City Baznas through the Jambi Smart City program, the supporting factors for zakat management at the Jambi City BAZNAS, and the influence of zakat on education at the Jambi City BAZNAS. This research uses descriptive qualitative research methods. The results of this research are that, there is a four-stage strategy for managing zakat in BAZNAS Jambi City which consists of planning, organizing, crucial mobilization in collection and distribution, and supervision. The supporting factor for Jambi City BAZNAS is the official and only body formed by the government, the Jambi City BAZNAS Official Website Portal, apart from through social media such as Instagram, Facebook and YouTube. And transfer payments are QR Code or QRIS. Meanwhile, the inhibiting factors are internal obstacles in collecting zakat funds, namely lack of public awareness, the traditional practice of people paying zakat directly and BAZNAS Jambi City having to compete with other zakat management institutions. The impact of zakat management for education at BAZNAS can help the community with their educational needs and ensure the sustainability of educational programs as an intergenerational accountability in Jambi City.